ACHIEVEMENT MOTIVATION BASED ON GENERATION - Erdiyanti, Yucky Putri (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
This study aims to describe the level of achievement motivation in female students. Achievement motivation referred to here is the need of an individual to solve difficult things well and independently, face obstacles and achieve high standards, and the courage to compete. The sample was taken with a purposive sample consisting of students from generation 2017, 2018, 2019 and 2020 FKIP Majalengka University. The instrument used is the achievement motivation questionnaire. The results of the study were analyzed using descriptive statistical analysis and t-test. The results show that there is no significant difference between the achievement motivation profiles of 2017, 2018, 2019 and 2020 students. The results of this study can be used as a basis for developing an academic guidance program for female students to increase student achievement motivation.Â